Enantio‐ and Diastereoselective Synthesis of Chiral Syn‐Aryl β‐Hydroxy α‐Amino Esters via Biocatalytic Dynamic Reductive Kinetic Resolution. Issue 7 (5th May 2021) - Zhang, Qing‐Chun; Lu, Zuo‐Lin; Hu, Chen; Zhu, Kejie; Jiang, Meifen; Huang, Zedu; Chen, Fener
Abstract: Development of an efficient, stereoselective, sustainable synthesis of chiral aryl β‐hydroxy α‐amino acids and their derivatives is of paramount importance, owing to the broad utility of these molecules in pharmaceutical application and asymmetric synthesis. We report a systematic study on ketoreductase (KRED)‐catalyzed dynamic reductive kinetic resolution (DYRKR) of aryl α‐amino β‐keto esters 6, furnishing 20 structurally diverse chiral syn ‐aryl β‐hydroxy α‐amino esters ( syn ‐(2 S, 3 R )‐7 ) in moderate‐to‐excellent isolated yield (up to 93%), along with moderate‐to‐excellent diastereoselectivity (up to >99 : 1 dr) and excellent enantioselectivity (mostly >99% ee). The practical synthesis potential of our developed method was showcased by the asymmetric, chemo‐enzymatic total synthesis of thiamphenicol (1 ). Abstract : A generic, efficient, and highly stereoselective synthesis of valuable chiral syn ‐aryl β‐hydroxy α‐amino esters ( syn ‐(2 S, 3 R )‐7 ) was developed through ketoreductase‐catalyzed dynamic reductive kinetic resolution of aryl α‐amino β‐keto esters 6 . The practical synthesis potential of this developed method was showcased by the asymmetric, chemo‐enzymatic total synthesis of thiamphenicol (1 ).